High quality draft genomes of the Mycoplasma mycoides subsp.mycoides challenge strains Afadé and B237 - Fischer, A.; Santana-Cruz, I.; Hegerman, J.; Gourle, H.; Schieck, Elise G.; Lambert, M.; Nadendla, S.; Wesonga, H.O.; Miller, R.A.; Vashee, S.; Weber, J.; Meens, J.; et al. (Springer, 2015)
Members of the Mycoplasma mycoides cluster’ represent important livestock pathogens worldwide. Mycoplasma mycoidessubsp. mycoides is the etiologic agent of contagious bovine pleuropneumonia (CBPP), which is still endemic in many parts of Africa. We report the genome sequences and annotation of two frequently used challenge strains of Mycoplasma mycoides subsp. mycoides, Afadé and B237. The information provided will enable downstream ‘omics’ applications such as proteomics, transcriptomics and reverse vaccinology approaches. Despite the absence of Mycoplasma pneumoniae like cyto-adhesion encoding genes, the two strains showed the presence of protrusions. This phenotype is likely encoded by another set of genes.